Activate the city center utility Measure the variables to activate the functionality of the city center case stady: AL-Kut city center - احسان عباس جاسم (Wasit Journal of Engineering Sciences)
Cities turn constantly grow and decay, Jobs many of its parts are constantly changing and therefore land use change, this change is a natural thing and the year of the ways of the universe, but in all cases and in all kinds of cities and all over the world is the city center is the city center of the most important of their parts and linked to the effectiveness of the city economic and social Hoitha closely linked to design the city center, whether small cities and concentric or large multicenter Disembowels main center axis performance career city it contains a large share of the buildings of all ages and styles and play an important and unique role in economic and social development so the city in order to be strong and prosperous must be right position and strong and free of problems. And make up the commercial, social and cultural center, this area is the most parts of the city easy access, where the focus of the urban transport network. The rapid growth of the Iraqi cities has led to a rapid transformation in the city centers, this transformation has not planned well and appropriately and led thus to the decline in the quality of life in cities, research has investigated the best ways and methods to determine the growth centers and Taktihaa trends to fit into the new job with the expansion of cities, as was the use of surveys and analysis of geographic information systems, and search out that urban centers are suffering a lot of problems and defects and should be reconsidered and planned development of appropriate its standards.